Water footprint of alfalfa hay production in Córdoba, Argentina - Bongiovanni, Rodolfo (2018)
In 2017, Argentina exported 58,848 t of alfalfa feed, for a value of nearly 19.8 million USD (UNcomtrade, 2018). Even though it only represents 0.7% of the world trade, it involves large amounts of virtual water in the product, which deserves the attention of the stakeholders of the alfalfa value chain, for a sustainable, efficient and equitable use of natural resources. In this sense, the water footprint is one of the family of environmental footprints that quantifies the amount of water consumed, evaporated and polluted. Worldwide, various activities consume or pollute water, but most of the water use occurs in agriculture (Hoekstra, Chapagain, Aldaya, & Mekonnen, 2011). Water consumption and pollution can be associated with specific activities, but until recently, there was little awareness to relate it to the structure of the global economy that supplies the various consumer goods and services. Hoekstra and Chapagain (2008) quantified the effects of consumption and trade on water resources use, by visualizing the hidden water in the products. Fresh water is a global resource, but due to the world trade, there is a spatial disconnection between the use of water resources and its consumers. For instance, this is the case of alfalfa hay exported from Argentina to the Middle East, i.e., production and final consumption are located in different places.